Low-cost high-conductivity graphene-based composite current collector and preparation method thereof
Through the roll -to -roll CVD heating and roller -to -roller process continuously preparing graphene base composite fluids, solve the problem of insufficient conductivity and mechanical stability of graphene film in existing technologies, and achieve a large scale of high -conductivity and low cost. Production improves the heat transfer and safety performance of lithium ion batteries.
Patent Information
- Application Number
- CN202411546928.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to produce graphene-based composite fluids with high conductivity and mechanical robustness on a large scale, resulting in significant challenges in internal heat transfer and local heat dissipation of lithium-ion batteries.
The roll -to -roll CVD heating method is continuously prepared to prepare defective copper foil or nickel foil to grow graphene film, and paint the metal source on the surface of the graphene film by rotating technology, and form a metal single atom or metal carbonized by high temperature sintering to form a metal single atom or metal carbonized. In the end, the roller -to -roller process was transferred to the high molecular material to prepare high -electrical graphene base composite albums.
Efficient and low-cost large-scale production of graphene-based composite current collectors has been achieved, which improves the conductivity and mechanical stability of the film, and improves the internal heat transfer and safety performance of lithium-ion batteries.
Smart Images

Figure CN119361713A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material synthesis, and relates to a low-cost high-conductive graphene-based composite current collector and a preparation method thereof, and in particular to a high-conductive graphene-based composite current collector continuously prepared by a roll-to-roll CVD heating method and a preparation method thereof. Background Art
[0002] High-energy lithium-ion batteries (LIBs) with efficient heat transfer capabilities are essential for safe operation in practical applications of energy storage, ranging from portable electronic devices to electric vehicles and grid energy storage transportation. The heat generated in the battery mainly comes from reversible heat generated by interfacial charge transfer, overpotential heat generated by mass transfer, and irreversible Joule heating generated by ohmic polarization. When the battery is in an abnormal operating state, heat accumulates locally due to slow heat transfer, resulting in violent thermal runaway when the threshold is reached. Therefore, controlling heat generation and improving heat transfer are crucial to eliminate battery thermal runaway. Although LIBs manufacturers have demonstrated sophisticated battery management systems and improved battery configurations to monitor the battery's thermal environment and accelerate heat transfer, there are still major challenges in improving internal heat transfer and dissipating local heat.
[0003] Fourier's law of heat conduction defines the current collectors (CCs) in LIBs as a bridge for the interaction between energy and external electrons, which can promote the movement of heat from the inside to the outside of the battery system, and provides a material-based theory for regulating heat transfer. Traditional CCs are mainly composed of metal elements, such as copper and aluminum, but due to the high concentration system generated by the need to transport 5 electrons, their thermal conductivity is 200~400 W m -1 K -1 In contrast, nonmetallic CCs materials with strong covalent bonds and small atomic mass can generate higher phonon velocities, i.e., fast particle core vibrations in the lattice, and exhibit enhanced thermal conductivity. As a typical nonmetallic material, two-dimensional layered graphene (Gr) exhibits π-π interactions between its layers, resulting in a tightly organized stacking structure that promotes phonon propagation and endows Gr with a high thermal conductivity of 5,300 W m at room temperature. -1 K -1 The remarkable theoretical conductivity of graphene sheets is 1.33 W, and the highly ordered arrangement and dense structure of graphene sheets can provide an effective heat transfer path. However, Gr films used as CCs on a large scale are still some distance away from commercialization due to the presence of a large number of defects and giant holes, insufficient thermal conductivity and mechanical robustness.
[0004] At present, the techniques for preparing graphene on a small scale have been widely recognized by researchers, such as filtration, electrospraying, spin coating and dip coating, all of which have successfully produced independent Gr films for button-type batteries. However, the large-scale production of uniform Gr films remains a challenge for the continuous production of commercial lithium batteries, especially power batteries, which usually require CCs of 100-1000 m. In addition, the limited flexibility, tensile strength and brittleness of current Gr films pose challenges to the large-scale preparation of soft-pack batteries, especially during the electrode winding process. At present, dense and defect-free Gr CCs have not been successfully prepared on an industrial scale and used as CCs to regulate heat transfer and improve the safety of LIBs. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to propose a low-cost and highly conductive graphene-based composite current collector material and a preparation method thereof, by adopting a "roll-to-roll" CVD heating method to continuously prepare a defect-rich copper foil or nickel foil self-grown graphene film, and coating a metal source such as nickel (Ni) and copper (Cu) on the surface of the graphene film by spin coating, and growing the required metal single atoms or metal carbides at the graphene defects by high-temperature sintering, and transferring them to polymer materials (PET, PI, etc.) by a simple laminating machine "roll-to-roll" technology, so as to prepare carbide-graphene-based composite current collectors in batches.
[0006] To achieve the above object, the present invention adopts the following technical solution: On the one hand, the present invention proposes a low-cost and highly conductive graphene-based composite current collector, comprising an organic film layer and a graphene film bonded to both sides of the organic film layer, wherein the internal defects of the graphene film are doped with metal source single atoms or metal source carbides, the organic film layer is PET or PI, and the metal source is one of nickel, copper, aluminum, and molybdenum.
[0007] On the other hand, the present invention provides a method for preparing the above-mentioned low-cost and highly conductive graphene-based composite current collector, and the specific preparation steps are as follows: Step (1): Place the metal substrate in the CVD heating cavity, evacuate the quartz tube, provide the gas precursor required for preparing the graphene film into the quartz tube, and continuously heat the quartz tube; during the heating process, the carbon-containing gas undergoes a cracking reaction when heated to produce activated carbon, which adheres to the target substrate and gradually forms a graphene film until the desired graphene film thickness is reached (the film thickness is adjusted by controlling the heating time), the heating element stops heating, and the metal substrate is removed from the heating cavity. By adjusting conditions such as temperature and gas flow rate, a defect-rich graphene film on a metal substrate is obtained.
[0008] Step (2): Dissolve a certain amount of metal source salt in a solvent. To promote the dissolution of the metal source salt solution, add a certain amount of alkaline solution to adjust the overall pH of the solution to alkaline to obtain a precursor solution. Then, the precursor solution is applied three times on the surface of the defect-rich graphene film by spin coating, and the mass and speed of the spin coating are controlled during the process. The coated product is dried in a drying oven at 60°C for 3h. Then, in an inert atmosphere, a heating rate of 2-10°C / min is used to perform calcination and heating treatment at a certain temperature to obtain a metal source-graphene-based composite current collector containing a metal substrate.
[0009] Step (3): Use a simple laminating machine’s “roll-to-roll” process to peel off the metal source-graphene-based film containing the metal substrate at a suitable speed, pressure and temperature to obtain a metal substrate and a metal source-graphene film, respectively, and laminate the metal source-graphene film on one side of an organic film (PET, PI, etc.). Then, laminate a metal source-graphene layer of the same structure on the other side of the organic film using the same operation to prepare a “sandwich” model, and finally obtain a reusable metal substrate and a current collector of a graphene / organic film / graphene composite structure.
[0010] Preferably, the metal substrate described in the above preparation method is one of copper foil, copper mesh, nickel foil and nickel mesh.
[0011] Preferably, the carbon-containing gas used for deposition in the above preparation method is one or more of methane, ethylene, propylene, and acetylene.
[0012] Preferably, the heating temperature for preparing the graphene film with substrate is 800-1050°C.
[0013] Preferably, the solvent described in the above preparation method is one or more of deionized water, ethanol and methanol.
[0014] Preferably, the alkaline solution described in the above preparation method is a mixture of one or more of ammonia water and urea.
[0015] Preferably, in order to further promote the dissolution of the metal source, the alkalinity range is about 8-11.
[0016] Preferably, during the lamination process, in order to ensure good adhesion between the layers, the lamination pressure needs to be adjusted within the range of 0.1-1 MPa.
[0017] Preferably, the lamination temperature ranges from 50° C. to 150° C., and the specific temperature needs to be adjusted according to the characteristics of the organic film material. The speed of the roll to roll is between 1 and 10 m / min.
[0018] Preferably, the calcination temperature in step S2 is 900-1200°C.
[0019] It should be noted that the above-mentioned "roll-to-roll" process is: growing graphene on metal foil by chemical vapor deposition (CVD) method, heating and pressing by the roller of the plastic sealing machine, so that the graphene layer and the heat-sensitive film are more closely attached together. The operation is called "roll-to-roll"; the above-mentioned "roll-to-roll" process is: the film material to be processed (such as graphene) will be gradually unfolded on the production line and sent to the roller system. The film material will be dried or cured by a heated roller after the coating or deposition process of a pair of rollers. This step can fix the coated graphene material on the substrate to ensure its performance and stability. This operation is called "roll-to-roll". The roll-to-roll process has the function of both bonding and peeling the two. After the metal substrate and the graphene-based film are peeled off, the present invention uses the roll-to-roll process to bond the graphene-based film to the surface of the organic film. The role of the organic film is to be responsible for receiving metal single atoms or metal carbides.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for continuously preparing a highly conductive graphene-based composite current collector by roll-to-roll CVD heating. During the preparation process, the roll-to-roll process can realize a continuous production process, greatly improve production efficiency, and is more suitable for large-scale production of graphene-based films than traditional batch production methods.
[0021] Since the prepared graphene film usually has defects, the conductivity of the graphene film will be reduced. The introduction of metal sources can compensate for these defects by doping or forming a metal-graphene interface, thereby improving the overall conductivity of the film. The thermal conductivity of the graphene film can be improved, and the performance of the graphene-based film current collector in lithium-ion batteries can be optimized by interacting with the thermal conductivity properties of graphene.
[0022] The substrate in the preparation process can be reused, reducing material costs. The high efficiency of the roll-to-roll process makes the recycling and reuse of metal substrates more economical and practical. And the transfer to organic thin films as current collector material substrates can greatly reduce the mass per unit area and effectively increase the energy density of the battery system.
[0023] Compared with the expensive equipment and complex processes (magnetron sputtering, vacuum evaporation, etc.) of traditional technologies, the technical solution of the present invention will help reduce the production cost of graphene films and is simpler and more effective, effectively promoting the large-scale production and application of graphene-based composite current collector technology; from the perspective of battery safety performance, the preparation method of highly conductive graphene-based films will improve the safety performance of composite current collectors.
[0024] In summary, the present invention adopts roll-to-roll CVD heating to continuously prepare graphene film and uses a simple laminating machine "roll-to-roll" technology to transfer to polymer materials (PET, PI, etc.) to batch prepare graphene-based composite current collectors. This method aims to replace metal current collectors, effectively alleviate thermal problems and improve battery safety. In addition, this method intends to develop a low-cost and continuous preparation process that can provide dense and flexible graphene-based current collectors on a hundred-meter scale to meet the requirements of large-scale energy storage devices such as LIBs soft-pack batteries, redox flow batteries, electrolyzers and fuel cells. The goal is to produce large-scale graphene-based composite current collectors, which can regulate the internal heat transfer of the battery and enhance the heat capacity, eliminating the aluminum thermite reaction and hydrogen evolution reaction in the battery. Significantly improve the uniform heat distribution during rapid charging and discharging to prevent combustion and explosion. This lightweight, conductive composite current collector also enables LIBs to operate at higher output energy and power. This new design provides a promising chemical engineering strategy for simultaneously improving thermal safety and energy density in large-scale energy storage solutions. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the graphene-based composite current collector structure.
[0026] Figure 2 It is a schematic diagram of the preparation principle of graphene-based composite current collector.
[0027] Figure 3 This is a physical picture of the graphene-based composite current collector prepared in the present invention. DETAILED DESCRIPTION
[0028] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0029] Figure 1 The schematic diagram of the structure of the prepared graphene-based composite current collector shows that the graphene-based composite current collector structure includes an organic film layer and a graphene film attached to both sides of the organic film layer. Since the prepared graphene film usually has defects inside, which will cause the conductivity of the graphene film to decrease, the graphene-based composite current collector prepared in this application compensates for these defects by doping or forming a metal-graphene interface, thereby improving the overall conductivity of the film. The internal defects of the graphene film are doped with metal source single atoms or metal source carbides. The organic film layer used in this application is PET or PI, and the metal source is one of nickel, copper, aluminum, and molybdenum.
[0030] Figure 2 This is a schematic diagram of the preparation principle of the graphene-based composite current collector for this application. The relevant process is as follows: Step 1: Batch produce defect-rich graphene films grown on copper foil through CAD; Step 2: Spin-coat the metal source on the surface of the graphene film; Step 3: Combine the defects in the graphene with the metal source through high-temperature sintering (forming single-atom metal or metal carbide); Step 4: Transfer the film in step 3 to a polymer material such as PET or PI by roll-to-roll method to form the final composite current collector. The actual picture of the prepared graphene-based composite current collector is shown in the figure below. Figure 3 The specific preparation example is as follows:
[0031] Embodiment 1:
[0032] 1. Place the nickel mesh substrate in the CVD heating cavity, evacuate the quartz tube, provide ethylene gas required for preparing the graphene film into the quartz tube, and continuously heat the quartz tube to 900°C; during the heating process, the gas reacts with the heat, and a graphene film gradually forms on the substrate. After the graphene film is formed, the heating element stops heating and the nickel mesh substrate is taken out of the heating cavity.
[0033] Second, ammonium molybdate was dissolved in an ethanol solution. To accelerate the dissolution, a certain amount of urea was added thereto, and the overall pH of the solution was adjusted to 9. The precursor was then applied three times on the substrate of the defect-rich graphene film by spin coating, during which the mass and speed of the spin coating were controlled, and the coated product was dried in a 60°C drying oven for 3 hours. Then, in an inert atmosphere, a heating rate of 2-10°C / min was used and calcined at 900°C to obtain a molybdenum carbide-graphene-based composite current collector containing a substrate.
[0034] 3. The molybdenum carbide-graphene-based film containing the metal substrate was peeled off at 0.5 MPa-80°C using the "roll-to-roll" process of a simple laminating machine to obtain the metal substrate and the molybdenum carbide-graphene film, respectively. The molybdenum carbide-graphene film was respectively attached to both sides of the PET organic film to prepare a "sandwich" model, and finally a reusable nickel mesh substrate and a graphene-based material / organic film / graphene composite structure composite current collector were obtained.
[0035] Embodiment 2:
[0036] 1. Place the copper foil substrate in the CVD heating cavity, evacuate the quartz tube, provide ethylene gas required for preparing the graphene film into the quartz tube, and continuously heat the quartz tube to 1000°C. During the heating process, the gas reacts with the heat, and a graphene film gradually forms on the substrate. After the graphene film is formed, the heating element stops heating and the copper foil substrate is taken out of the heating cavity.
[0037] 2. Dissolve copper chloride in a mixed solution of ethanol and water. To accelerate dissolution, add a certain amount of ammonia water to adjust the overall pH of the solution to 11. Then, the precursor is applied three times on the substrate of the defect-rich graphene film by spin coating. During the process, the quality and speed of the spin coating are controlled, and the coated product is dried in a drying oven at 60°C for 3h. Then, in an inert atmosphere, the heating rate is 2-10°C / min and the calcination treatment is carried out at 1200°C to obtain a copper carbide-graphene-based composite current collector containing a substrate.
[0038] 3. The copper carbide-graphene-based film containing the metal substrate was peeled off at 1.0 MPa-100°C using the "roll-to-roll" process of a simple laminating machine to obtain the metal substrate and the copper carbide-graphene film respectively, and the copper carbide-graphene film was respectively attached to both sides of the PET organic film to prepare a "sandwich" model, finally obtaining a reusable copper foil substrate and a graphene-based material / organic film / graphene composite structure composite current collector.
[0039] Performance Test:
[0040] The graphene film resistance test result of the graphene-based composite current collector prepared in Example 1 is 2.953 KΩ / □, where □ means square resistance, and the graphene film resistance test result of the graphene-based composite current collector prepared in Example 2 is 3.041 KΩ / □, which proves that the graphene-based composite current collector prepared by the technical solution of the present invention has less internal resistance, thereby reducing energy loss and improving the overall energy efficiency of the battery. Compounding with lightweight materials (such as polymer PET, PI materials) can significantly reduce the weight of the current collector while maintaining good conductive properties, thereby improving the energy density of the battery system.
[0041] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A low-cost, highly conductive graphene-based composite current collector, characterized in that: It includes an organic film layer and a graphene film attached to both sides of the organic film layer, wherein the internal defects of the graphene film are doped with metal source single atoms or metal source carbides, the organic film layer is PET or PI, and the metal source is one of nickel, copper, aluminum and molybdenum.
2. A method for preparing a low-cost, high-conductivity graphene-based composite current collector according to claim 1, characterized in that: The steps include: S1: placing a metal substrate in a CVD heating cavity, evacuating a quartz tube, providing a gas precursor required for preparing a graphene film into the quartz tube, and continuously heating the quartz tube; during the heating process, the carbon-containing gas undergoes a cracking reaction when heated to produce activated carbon, which adheres to the metal substrate and gradually forms a graphene film until the desired graphene film thickness is reached, then the heating element stops heating and the metal substrate is taken out of the heating cavity; obtaining a defect-rich graphene film on the metal substrate; S2: dissolving a certain amount of salt of a metal source in a solvent, and adding a certain amount of alkaline solution thereto, adjusting the overall pH of the solution to alkaline, and obtaining a precursor solution; then coating the precursor solution on the surface of the defect-rich graphene film by spin coating, controlling the mass and speed of the spin coating, and drying the coated product in a drying oven; then, in an inert atmosphere, using a heating rate of 2-10°C / min, calcining at a certain temperature to obtain a metal source-graphene-based composite current collector containing the above-mentioned metal substrate; S3: The graphene layer of the metal source-graphene-based composite current collector containing the above-mentioned metal substrate is peeled off by a "roll-to-roll" method at a suitable speed, pressure and temperature to obtain a metal substrate and a metal source-graphene film respectively, and the metal source-graphene film is laminated on one side of the organic film and the metal source-graphene film is laminated on the other side of the organic film by the same operation to prepare a "sandwich" model, and finally a reusable metal substrate and a current collector of a graphene / organic film / graphene composite structure are obtained.
3. The method for preparing a low-cost and highly conductive graphene-based composite current collector according to claim 2, characterized in that: The metal substrate is one of copper foil, copper mesh, nickel foil and nickel mesh.
4. The method for preparing a low-cost and highly conductive graphene-based composite current collector according to claim 2, characterized in that: The carbon-containing gas used for deposition in the above preparation method is one or more of methane, ethylene, propylene and acetylene.
5. The method for preparing a low-cost and highly conductive graphene-based composite current collector according to claim 2, characterized in that: The heating temperature in step S1 is 800-1050°C.
6. The method for preparing a low-cost and highly conductive graphene-based composite current collector according to claim 2, characterized in that: The solvent described in step S2 is one or more of deionized water, ethanol, and methanol.
7. The method for preparing a low-cost and highly conductive graphene-based composite current collector according to claim 2, characterized in that: The alkaline solution described in step S2 is a mixture of one or more of ammonia water and urea, and the pH value is adjusted to an alkaline range of 8-11.
8. The method for preparing a low-cost and highly conductive graphene-based composite current collector according to claim 2, characterized in that: During the lamination process, in order to ensure good adhesion between layers, the lamination pressure is 0.1-1 MPa.
9. The method for preparing a low-cost and highly conductive graphene-based composite current collector according to claim 2, characterized in that: The laminating temperature ranges from 50°C to 150°C, and the roll-to-roll speed ranges from 1 to 10 m / min.
10. The method for preparing a low-cost and highly conductive graphene-based composite current collector according to claim 2, characterized in that: The calcination temperature in step S2 is 900-1200°C.